APLIKASI 3D VIRTUAL TOUR KAMPUS DENGAN TEKNOLOGI IMERSIF - Fahrul Razi; Shevti Arbekti Arman (Jurnal Informatika, 2026)
Digital transformation demands higher education institutions to adopt innovative and interactive promotional strategies that effectively reach prospective students. This study aims to develop a 3D Virtual Tour application using immersive technology as a campus promotion medium, implemented through the 3DVista platform. The development process follows the Multimedia Development Life Cycle (MDLC), starting from user needs identification, interface and navigation design, 360Â° panorama content documentation, to integration into an interactive application. Usability evaluation was conducted on 20 respondents using the System Usability Scale (SUS), resulting in an average score of 87.5, indicating a high level of user satisfaction. The findings demonstrate that 3D virtual tour-based promotional media not only offer an engaging digital experience but are also effective in building a modern and inclusive institutional image. This innovation is expected to serve as an adaptive, technology-based promotional alternative aligned with Asta Cita 6.